Do Oil Shocks Matter for Inflation Rate in Russia: An Empirical Study of Imported Inflation Hypothesis - Bass, Alexander (International Journal of Energy Economics and Policy, 2019)
In this article we aim to assess the impact of world oil prices shocks on inflation dynamics in Russia. Based on the data for the period 2010-2017 for Russia we explore the relationship between world oil prices (Brent), exchange rate and Russian consumption price index using a VEC framework. For detecting the casual relationship, Granger causality test is applied. The results of the study show that oil prices, exchange rate and consumer inflation in Russia are cointegrated in the long-run. The results of the Wald test in the short run show that there is a statistically significant relationship between changes in world oil prices, exchange rate and CPI. Keywords: oil prices, inflation, exchange rate, vector error correction JEL Classifications: E31, F31, Q41 DOI: https://doi.org/10.32479/ijeep.7359